2010
DOI: 10.1037/a0017023
|View full text |Cite
|
Sign up to set email alerts
|

Practicing clinical psychologists’ provision of sexual health care services.

Abstract: Practicing clinical psychologists are likely to work with sexual health concerns as part of their clinical practice because of high prevalence rates and sexual problems as symptoms of mental or physical health problems and their pharmacological treatment. However, the majority of clinicians do not receive didactic or supervised clinical training. This survey of 188 practicing clinical psychologists in one Canadian city confirmed that, despite lack of training, many clinicians discussed sexual health concerns w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
68
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(75 citation statements)
references
References 27 publications
6
68
0
1
Order By: Relevance
“…Of these clinicians, many do not feel competent or comfortable treating such issues (Ayres and Haddock 2009;Reissing and Giulio 2010). Although most MHPs report beliefs that IP use and sex related issues are a problem (Ayres and Haddock 2009;Swisher 1995), the lack of training and education about these issues may affect MHPs' attitudes, perceptions, and beliefs toward them.…”
Section: Methodsmentioning
confidence: 90%
“…Of these clinicians, many do not feel competent or comfortable treating such issues (Ayres and Haddock 2009;Reissing and Giulio 2010). Although most MHPs report beliefs that IP use and sex related issues are a problem (Ayres and Haddock 2009;Swisher 1995), the lack of training and education about these issues may affect MHPs' attitudes, perceptions, and beliefs toward them.…”
Section: Methodsmentioning
confidence: 90%
“…As with graduate training, post-internship education consists of vicarious therapy experience, independent study, and verbal persuasion; it also includes peer consultation (Reissing & Di Giulio, 2010). These experiences likely result in increased confidence about addressing sexual issues with clients.…”
Section: Development Of Self-efficacy Beliefsmentioning
confidence: 94%
“…That is, many individuals will not discuss sexual issues unless the clinician initiates the conversation and demonstrates an openness and comfort with this topic even though their sexual concerns are relevant to the therapeutic goals (Hegarty, Brown, & Gunn, 2007;Metz & Seifert, 1990;Rubin,2004). Reissing and Di Giulio (2010; see also Miller & Byers, 2009) found that over half of the clinical psychologists they surveyed rarely or never asked clients about their sexual well-being. To be effective at developing strategies to enhance the likelihood that clinicians will address sexual concerns with their clients, it is important to identify factors that influence their willingness to do so.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Il serait intéressant, dans l'avenir, de sonder les différents professionnels de la santé en péri-natalité pour vérifier ces perceptions. Après tout, il est fréquent que des professionnels de la santé ne se sentent pas à l'aise de discuter de la sexualité, et ce, peu importe le domaine d'activité (Church, de Koning, Hilber, Ormel et Hawkes, 2010 ;de Pierrepont et Polomeno, 2015 ;Reissing et Di Giulio, 2010). Il serait aussi approprié de questionner et de spécifier les raisons sous-jacentes à cet inconfort, notamment le manque de connaissances et de formation en sexualité chez les professionnels.…”
Section: Discussionunclassified